Synovial Sarcoma: A Comparative Study of Immunohistochemical Markers (Bcl2 and CD99) versus Fluorescence In Situ Hybridization - G, Chandana; Bhopal, Triveni; K, Vijaya Durga; Usha, Mahesh Kumar; Singh, Rajput S.A Kiran (Annals of Pathology and Laboratory Medicine, 2024)
Background Synovial Sarcoma (SS) is a mesenchymal tumor, which displays a variable degree of epithelial differentiation including gland formation, and has a specific chromosomal translocation t(x;18)(p11;q11) that leads to the formation of an SS18-SSX fusion gene. The diagnostic gold standard for Synovial Sarcoma is the demonstration of the characteristic translocation between the SS18 (SYT) gene on chromosome 18 and one of the three SSX genes (SSX1, SSX2, or rarely SSX4) on chromosome X {t(x;18)(p11.2;q11.2)} [1, 2]. The use of these techniques is limited by many practical issues like cost and specialized equipment availability. Thus, in practice, the diagnosis of SS is usually based on histological examination and immunohistochemistry (IHC) [3, 4]. Our objective is to study the expression of Bcl2 and CD99 in Synovial Sarcoma and to compare the results with fluorescence in situ hybridization (FISH) to evaluate the sensitivity of Bcl2 and CD99 in the diagnosis of Synovial Sarcoma. Material and Methods Tissue was processed and microtomy was done. Hematoxylin and eosin (H&E) staining was performed. IHC was carried out on all sections using CD99, Bcl2, EMA, CK, and all other markers which aid in differentiating SS from its mimics. All the formalin-fixed paraffin-embedded (FFPE) tissue samples from 50 histologically diagnosed Synovial Sarcoma cases, which showed Bcl2 and CD99 positivity, were submitted for FISH.. Results Forty cases out of fifty histologically and Bcl2 & CD99 positive Synovial Sarcoma cases were positive for FISH, showing the t(x;18)(p11.2;q11.2) translocation. Conclusion Bcl2, CD99, Vimentin, EMA, and PCK are routinely used markers in the diagnosis of Synovial Sarcoma. It is found that Bcl2 and CD99 are highly sensitive markers in the initial diagnosis and management of Synovial Sarcoma in patients who cannot afford cytogenetic studies.